When Good Conservation Becomes Good Economics : Kenya’s Vanishing Herds - Damania, Richard; Desbureaux, Sebastien; Scandizzo, Pasquale Lucio; Mikou, Mehdi; Gohil, Deepali; Said, Mohammed (World Bank, Washington, DC, 2019)
It is no exaggeration to state that Kenya’s wildlife has done much to shape the image and development fortunes of the country. Today tourism is among Kenya’s top sources of foreign exchange, dominates the service sector, and contributes significantly to employment, especially in rural areas where economic opportunities are limited. The typical international tourist arrives on a package tour that may include a safari, a visit to the beach, or both. It is safari tourism, however, that generates the most employment and economic activity across the country. But the wildlife that has lured travelers to Kenya by the planeload is in dramatic decline. In the past three decades, the country has lost more than half of its wildlife. Wild herds that once roamed freely across the borders of Kenya and Tanzania have shrunk dramatically in numbers and vanished completely from much of the North. Perhaps most troubling is that recent monitoring of wildlife populations suggests that long-term declines of many of the charismatic species that attract tourists like lions, elephants, giraffes, impalas, and others are occurring at the same rates within the country’s national parks as outside of these protected areas. This report identifies with greater precision the drivers of land conversion from natural habitats to other uses, and examines the extent to which land conversion leads to the extirpation of wildlife and the loss of tourism incomes.